An Integrative Review of Return to Driving After Concussion in Adolescents. (February 2021) - Jain, Divya; Arbogast, Kristy B.; Master, Christina L.; C. McDonald, Catherine
Concussion is a common injury among adolescents. It is unknown how a concussion affects driving behavior and performance in adolescents. Although there are guidelines for return to learn, exercise, and sports that school nurses can help support in school, little is known about return to driving after concussion. The goal of this integrative review was to summarize the current literature on return to driving after concussion in adolescents. Six articles published between 2016 and 2020 were included in the review. Physicians and nurse practitioners find providing driving recommendations to adolescents to be appropriate; however, they are unclear what metrics to use to determine whether a patient is fit to drive. Future studies should explore clinical predictors of readiness to return to driving in adolescents. School nurses have an opportunity to support adolescents in their resumption of typical activities after concussion including school, sports, and, as more evidence becomes available, driving.